THE HISTORY OF THE ESTABLISHMENT OF DIPLOMATIC RELATIONS BETWEEN JAPAN AND THE OTTOMAN TURKISH STATES. DURING SULTAN ABDULHAMID - Jahongir Yursinboyev (Western European Studies, 2024)
This article analyzes the historical period created for the establishment of relations between the Ottoman and Japanese states. The historical conditions of both countries have been analyzed
Keywords: Japan; Ottoman; Abdul Hamid II; Tokugawa